2019
DOI: 10.1055/s-0039-1688563
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between Computed Tomography and Magnetic Resonance Imaging Measurements of Tibial Tubercle–Trochlear Groove Distance for Patients with or without Patellofemoral Instability: A Systematic Review and Meta-analysis

Abstract: AbstractThe tibial tubercle–trochlear groove (TT–TG) distance was originally described for computed tomography (CT) but has recently been used on magnetic resonance imaging (MRI) without sufficient evidence demonstrating its validity on MRI. The current review aims to evaluate (1) whether there is a difference in the TT–TG distances measured using CT and MRI, (2) whether both the TT–TG distances measured using CT and MRI could be used to differentiate between patients with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
3
37
0
2
Order By: Relevance
“…Measurements made by CT and MRI have been investigated extensively in adults. 2,8,14,15,[19][20][21] Some researchers have investigated TT-TG measured on MRI in skeletally immature patients, who have high occurrence of PI. 4,6,10,17,25 However, no research has compared TT-TG distance measured between the 2 modalities in a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements made by CT and MRI have been investigated extensively in adults. 2,8,14,15,[19][20][21] Some researchers have investigated TT-TG measured on MRI in skeletally immature patients, who have high occurrence of PI. 4,6,10,17,25 However, no research has compared TT-TG distance measured between the 2 modalities in a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 5 studies, Tan et al 20 found an MD of 1.79 mm (95% CI, 0.91-2.68 mm) between CT and MRI for adults. The difference between the 2 modalities in children seems relatively greater than that in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The odds of not being able to return to sports postoperatively as compared with preinjury was 2.78; however, this was not statistically significant, with the 95% CI being 0.53 to 14.68 (►Fig. 6). No publication bias was identified (p ¼ 0.385) (►Fig.…”
Section: Return To Sportsmentioning
confidence: 96%